2009
DOI: 10.1111/j.1525-142x.2009.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic muscle development in direct and indirect developing marine flatworms (Platyhelminthes, Polycladida)

Abstract: We compared embryonic myogenesis of the direct-developing acotylean polyclad Melloplana ferruginea with that of Maritigrella crozieri, a cotylean that develops via a larval stage. Fluorescently labeled F-actin was visualized with laser confocal microscopy. Developmental times are reported as percentages of the time from oviposition to hatching: 7 days for M. crozieri and 22 days for M. ferruginea. The epithelium began to form at 30% development in M. crozieri and at 15% development in M. ferruginea. Random myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…In addition, X-shaped muscles are present in all three species. The latter are also found in M. crozieri, although the authors do not associate these with the oral hood in this species (Bolan˜os and Litvaitis 2009). In H. inquilina, the oral retractor muscles extend from the apical pole into posterior direction (Reiter et al 1996), similar to the situation found in S. sanjuania (Fig.…”
Section: Myogenesis In Basal Rhabditophoran Platyhelminthesmentioning
confidence: 64%
See 3 more Smart Citations
“…In addition, X-shaped muscles are present in all three species. The latter are also found in M. crozieri, although the authors do not associate these with the oral hood in this species (Bolan˜os and Litvaitis 2009). In H. inquilina, the oral retractor muscles extend from the apical pole into posterior direction (Reiter et al 1996), similar to the situation found in S. sanjuania (Fig.…”
Section: Myogenesis In Basal Rhabditophoran Platyhelminthesmentioning
confidence: 64%
“…The oral hood of M. crozieri appears to express only circular muscles, whereas in S. sanjuania and P. canadensis diverse retractor muscles, which connect to the stomodeum, are found (Bolan˜os and Litvaitis 2009). In addition, X-shaped muscles are present in all three species.…”
Section: Myogenesis In Basal Rhabditophoran Platyhelminthesmentioning
confidence: 97%
See 2 more Smart Citations
“…This situation is thus more similar to other studied spiralians and can be considered to be the ancestral state to all Platyhelminthes. Studies are, however, scarce and have mostly focused on the formation of the larval neuromuscular system (Younossi- Hartenstein and Hartenstein 2000 ;Bolaños and Litvaitis 2009 ;Rawlinson 2010Rawlinson , 2014Semmler and Wanninger 2010 ). In indirect developing polyclads, an initial apical helicoid muscle develops into an orthogonal grid of longitudinal and circular muscles, which corresponds to the adult body wall musculature.…”
Section: Organogenesis In Platyhelminthesmentioning
confidence: 99%